Adaptive immune response to lipoproteins of Staphylococcus aureus in healthy subjects. Issue 20 (3rd August 2016) - Vu, Chi Hai; Kolata, Julia; Stentzel, Sebastian; Beyer, Anica; Gesell Salazar, Manuela; Steil, Leif; Pané‐Farré, Jan; Rühmling, Vanessa; Engelmann, Susanne; Götz, Friedrich; van Dijl, Jan Maarten; Hecker, Michael; et al.
Abstract : Staphylococcus aureus is a frequent commensal but also a dangerous pathogen, causing many forms of infection ranging from mild to life‐threatening conditions. Among its virulence factors are lipoproteins, which are anchored in the bacterial cell membrane. Lipoproteins perform various functions in colonization, immune evasion, and immunomodulation. These proteins are potent activators of innate immune receptors termed Toll‐like receptors 2 and 6. This study addressed the specific B‐cell and T‐cell responses directed to lipoproteins in human S. aureus carriers and non‐carriers. 2D immune proteomics and ELISA approaches revealed that titers of antibodies (IgG) binding to S. aureus lipoproteins were very low. Proliferation assays and cytokine profiling data showed only subtle responses of T cells; some lipoproteins did not elicit proliferation. Hence, the robust activation of the innate immune system by S. aureus lipoproteins does not translate into a strong adaptive immune response. Reasons for this may include inaccessibility of lipoproteins for B cells as well as ineffective processing and presentation of the antigens to T cells.